Labour productivity and development of carbon competitiveness industry-level evidence from Europe - Kaitila Ville (The Research Institute of the Finnish Economy (ETLA), 2023)
A drastic decline in global greenhouse gas (GHG) emissions is needed to stop the climate change. This requires a variety of political and market mechanisms. Europe is globally at the forefront among the industrialised countries in reducing its GHG emissions. We analyse the development of emission intensities - GHG emissions relative to value added produced - and use a panel data to further our understanding of their evolution at the level of industries in 2008-2020 in Europe. We find that labour productivity is negatively associated with changes in GHG-emission intensities. Furthermore, higher investments, higher carbon prices within the ETS mechanism, and higher environmental taxes are associated with lower GHG-emission intensities. Consequently, policies that promote productivity growth and financial incentives to decrease emissions lead to lower emissions. Finland's carbon competitiveness, as measured by relative GHG-emission intensities, varies by industries.
Keywords: C23; O44; Q54; Q56; 330; Greenhouse gas emissions (GHG); GHG-intensity; Carbon competitiveness; Productivity; ETS